Quels critères utiliser pour questionner la qualité pédagogique des stages cliniques ? - Viviane Vierset; Mariane Frenay; Denis Bédard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The objective of this article is to propose some tracks to analyze the pedagogical quality of training in medicine. The conceptual framework of “Authentic Situated Learning and Teaching” (AECA) constitutes the main theoretical background (Bédard, Frenay, Turgeon & Paquay, 2000; Frenay & Bédard, 2004) from which this work has been realized. It is based on two fundamental pedagogical principles that are intertwined: authenticity of the learning environment and cognitive apprenticeship. Associated with each principle are conditions that aim at improving the quality of teaching and learning in any pedagogical environment, such as a cursus of clinical trainings.Based on the conceptual framework of AECA, we identified quality criteria to evaluate the clinical field considered. Thus, translated in a series of questions, the AECA framework allows taking a step back to raise questions challenging the context of clinical trainings, particularly about its practices and pedagogical postures revealed in situ. The list of questions is a preliminary exploration project (re)structuring clinical placements.